Bộ bài thi thử kiểm tra trình độ tiếng Trung mới HSK cấp độ 2 - 新汉语水平考试模拟试题集 HSK二级 - Liu, Hongying (Beijing Language & Culture Unive, 2010)
New Chinese Proficiency Test HSK Stimulated Tests altogether have six levels. It is a collection of simulated tests written by experienced TCSL teachers according to the general requirements of New Chinese Proficiency Test HSK (Chinese Proficiency Test) newly enacted by Hanban. All the stimulated tests have been used in preparation classes and proved to help examinees improve their examination skills and Chinese in a short time. Each level is composed of 10 model tests, covering virtually all the words and grammar points required in the Syllabus and including Chinese and English introduction to testing points of new HSK. CD of MP3 files of listening parts in model tests are included. This book is level 2, requiring a vocabulary of at least 300 words.